Study on Stability Analysis Method and Treatment Measure of Dragline Stripping Bench in Hedaigou Open-Pit Coal Mine - Zhen Wang; Pengfei Qin; Ang Li; Liying Zhu (Advances in Civil Engineering)
Due to the steep slope angle and fractured rock mass of the dragline stripping bench in Hedaigou open-pit coal mine, dragline stripping bench failure frequently occurs. Conventional slope stability analysis methods are based on the assumption of shear-dominated failure mechanisms. In contrast, dragline stripping bench stability is influenced by both tension and shear failure modes, which makes conventional slope stability analysis methods unsuitable for dragline stripping bench stability assessment. In order to solve these problems, this article abandons the conventional mechanical analysis methods and innovatively explores slope stability analysis from the perspectives of energy and velocity. On this basis, takes dragline stripping bench in Hedaigou open-pit coal mine as engineering background, analyzes the potential failure mode of dragline stripping bench and establishes a stability analysis method for dragline stripping bench considering the combined failure characteristics of tension and shear, then reveals the influence of location and depth of tension fractures on stability of dragline stripping bench. Meanwhile, based on an understanding of bonding properties and diffusion behavior of polyurethane materials, treatment measures of dragline stripping bench are proposed, and treatment effects are reasonably evaluated by combining numerical simulation methods. The results show that the potential failure mode of the dragline stripping bench in Hedaigou open-pit coal mine is a combination failure of tension and shear. When the distance between tension fractures and slope crest line is 5–16 m, the dragline stripping bench is most prone to failure. When tension fractures appear in this area and develop to a certain depth, it is recommended to use polyurethane grouting for dragline stripping bench treatment, with a corresponding grouting height of 1.4–3.5 m. Through treatment measures of polyurethane grouting, the displacement monitoring data gradually tends to be stable, and the velocity monitoring data gradually approaches 0 at the tension fractures position, indicating that the stability of the dragline stripping bench has been significantly improved.